MENINGKATKAN HASIL BELAJAR PKN TENTANG PENERAPAN NILAI- NILAI PANCASILA MELALUI MODEL PROJECT BASED LEARNING (PJBL) DI KELAS IV SDN 8 KABILA KABUPATEN BONE BOLANGO - Alimun, Nur Marhamah; Pomalingo, Samsi; Ismail, Reska Putri (Lembaga Pendidikan dan Penelitian Manggala Institute, 2025)
This research aims to improve Civic Education (PKn) learning outcomes regarding the application of Pancasila values ​​through the Project Based Learning (PJBL) model in class IV at SDN 8 Kabila, Bone Bolango Regency. The method used in this research is Classroom Action Research. The research subjects consisted of 15 class IV students. Data was collected through observation, interviews and documentation. Data collection techniques include observation, tests, and documentation. The research results show that implementing the PJBL model can increase student involvement in learning and their understanding of Pancasila values. Students are more active in discussions and collaboration when working on projects, which leads to significant improvements in learning outcomes. Apart from that, the PJBL model also helps students to relate the concept of Pancasila to real situations in everyday life. Thus, the application of the Project Based Learning model has proven to be effective in improving Civics learning outcomes and forming good student character in accordance with Pancasila values. It is hoped that this research can be a reference for teachers in implementing more interactive and relevant learning methods. The learning outcomes of students in cycle I who reached the KKM in Civics subject content were 6 students with a percentage of 55%. Meanwhile, in cycle II there was an increase of 13 students with a percentage of 87%. The conclusion in this research is that using the Project Based Learning (PJBL) model can improve student learning outcomes in class IV at SDN 8 Kabila, Bone Bolango Regency.